Parâmetros assistenciais em saúde bucal: comparação entre duas programações do atendimento clínico no serviço público - Garbin, Artênio José Insper [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Diniz, Diego Garcia [UNESP] (Fundacao Edson Queiroz, 2012)
Objective: To compare two forms of scheduling clinical dental care for the oral health teams (OHT) included in the strategy of family health, regarding productive aspects of assistance. Methods: Two OHT worked concurrently, using two methods of clinical care: the parameter recommended by the Ministry of Health Ordinance No. 1101, 2002, which establishes 03 dental visits per hour (c/h) per team, and a Testing model, with 02 c/h, being each method applied for a period of 615 hours. The quantitative data was collected in OHTs’ daily production spreadsheets, covering the following items: the number of dental visits (initial, for maintenance and for emergency procedures), procedures performed, consumption of material and sterilization cycles. Data was compared and statistically analyzed through the BioStat 5.0 by applying the paired t-test (p <0.05). Results: Under the Ministerial method and the Testing model, were performed, respectively, 288 and 365 first dental visits, 921 and 686 return dental visits, 167 and 172 emergency dental attendances, with 469 and 110 fouls, 212 and 327 treatments were finished and 2501 and 3046 dental procedures were realized. Among eleven analyzed consumables, five were consumed in smaller quantities in the Testing model: gloves (9%), anesthesia (38%), anesthetic needle (34%), suture material (24%) and aspirators (11%), while the six remaining items presented similar consumption rates between the two models. Conclusions: The testing model revealed to be more productive and economical.

Objetivo: Comparar duas formas de programação do atendimento clínico odontológico de equipes de saúde bucal (ESB) inseridas na estratégia de saúde da família em relação aos seus aspectos produtivos assistenciais. Métodos: Duas ESB executaram, concomitantemente, duas metodologias de atendimento clínico: o parâmetro recomendado pela portaria do Ministério da Saúde Nº 1101 de 2002, que estabelece 03 consultas por hora (c/h) por equipe e um modelo Teste, com 02 c/h, sendo cada método aplicado por um período de 615 horas. Os dados quantitativos foram coletados através das planilhas de produção diária das ESB, em que constavam os seguintes itens: quantidade de consultas (iniciadas, de manutenção e de urgência), número de procedimentos executados, consumo de material e ciclos de esterilização. Os mesmos foram comparados entre os modelos e avaliados estatisticamente, através do programa Bioestat 5.0, aplicando-se o Teste t pareado (p<0,05). Resultados: No método Ministerial e no Teste, foram realizadas, respectivamente, 288 e 365 primeiras consultas, 921 e 686 consultas de manutenção, 167 e 172 consultas de urgência, com 469 e 110 faltas de pacientes, finalizando 212 e 327 tratamentos e executando 2501 e 3046 procedimentos. Dos onze itens de consumo analisados, cinco foram utilizados em menor quantidade no modelo Teste: luvas (9%), anestésico (38%), agulha anestésica (34%), fio agulhado (24%) e sugador (11%), enquanto os 06 restantes tiveram consumos semelhantes entre os modelos. Conclusão: O modelo Teste revelou-se mais produtivo e econômico.
Oral health care parameters: comparison between two methods of scheduling clinical dental care in the public service
Keywords: Health services; Family health; Oral health; Efficiency organizational; Serviços de saúde; Saúde da família; Saúde bucal; Eficiência organizacional